Multifaceted protocol in biotechnology - Amid, Azura (Springer Nature, 2018)
Multifaceted Protocol in Biotechnology consists of methods and techniques commonly used in biotechnology studies. There are four sections covered in this book –bioprocess, whole cells and isolated biocatalyst, characterization of biochemical products, and cell isolation and culture. A brief introductory supported with each protocol/method designated for better understanding. The first part of this book consists of recent methodologies for discovering the whole cell and isolated biocatalysts as to improve their current properties which significantly contribute to the development of new industrial processes. It encompasses five chapters covering topics on the mutagenesis of cyanobacteria, site-directed mutagenesis on a plasmid, construction of metagenomics DNA libraries, and isolation of bacteria producing enzymes. It is expected that these chapters will bring about the current status of research and developments in biotechnology area with a critical perspective. The second part covers four chapters covering researches in modern biotechnology focusing in bioprocess areas such as biofuel, catalyst, microbial, and enzyme. It is expected that these chapters will bring about the current methods of research and developments in bioprocess areas. The third part of this book encompasses topics such as preparation and characterization of some biochemical products such as nitrocellulose, proteins, poly(lactic acid), and electrochemical transducer for the biosensor. It consists of five chapters covering reviews of the current state of the characterization of biochemical products that may be useful in identifying biochemical products with a different approach. Characterization of biochemical products is an important part of the early stage of process development of biochemical products. It is due to ensuring specification of the product especially its quality and consistency of the product is met before commercialized. It is expected that these chapters will benefit other researchers to apply in determining the characteristics of their biochemical products. The final part covers cell isolation and culture, encompassing a wide range of multifaceted areas including chemistry, biology, engineering, and statistics. This part comprises of five chapters covering the method for isolation of bacterial strain from contaminated soil, monitoring the growth of plant cell suspension culture, culturing and maintaining mammalian cell culture, integrated data analysis model for screening cell line producer, and skim latex serum as an alternative nutrition for bacterial growth. Advances in cell isolation and cultures technology discussed in these chapters are not a means to an end in this research area but as a paved path for other researchers to explore.